Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Kualitas Laba pada Perusahaan Sektor Industrial yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Hermansyah, Hermansyah; Fahmi, Muhammad; Rusmita, Sari; Espa, Vitriyan; Kurniawan, Rudy (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine, identify, and analyze the influence of profitability, leverage, and firm size variables on earnings quality. The research employs a quantitative approach using secondary data obtained from the annual financial statements of industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the observation period from 2021 to 2024. The companies’ financial statements were obtained directly from their official websites as well as from the website www.idx.co.id. The sample was selected using purposive sampling techniques based on specific, predetermined criteria, resulting in a total of 195 final observational data points that met the research requirements. All collected data were then processed through several analytical procedures, including Descriptive Statistical Analysis, Classical Assumption Tests consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, Multiple Linear Regression Test, and Hypothesis Testing, with the aid of IBM SPSS (Statistical Package for the Social Sciences) version 26. Based on the analysis results, it was found that profitability affects earnings quality, while leverage has an impact on earnings quality; however, firm size does not have a significant effect on earnings quality.